Integrative Geospatial Analysis of Agricultural Land Resilience Using NDVI-Based Remote Sensing and GIS: Spatio-Temporal Impacts of Urbanization in Sleman Regency (2017–2022) - Pamungkas, Guntur Bagus; Firmansyah, Muhammad Reffi; Tamara, Anindya Putri; Zainul, Rahadian (Society of Visual Informatics, 2025)
This study delves into the dynamics of agricultural health in Sleman Regency, Yogyakarta Special Region Province, Indonesia, spanning the years 2017 to 2022. By integrating Geographic Information System (GIS) techniques with NDVI-based remote sensing using Landsat imagery from the USGS, our research aims to comprehend the spatio-temporal patterns and transformations in agricultural land health over the study period. The primary objectives encompass understanding these alterations and assessing how urbanization and land utilization impact the well-being of agricultural lands in Sleman Regency. The analytical framework incorporates geospatial processing using QGIS to classify and visualize vegetation health changes, enabling spatially explicit interpretation of land degradation trends. Throughout the 2017–2022 analysis period, a concerning and consistent decline in healthy agricultural lands was observed. By 2022, only 4581.56 hectares of agricultural land remained in a healthy state, constituting a mere 0.011% of the total region, while the expanse of unhealthy land surged from 1109.48 hectares in 2017 to 1160.8 hectares in 2022. This shift underscores a distressing deterioration in the health of agricultural plants due to diminished agricultural land. The geospatial analysis reveals a notable encroachment pattern from urban expansion zones into previously fertile areas, highlighting the urgency for integrated spatial planning. To counter this trend, proactive protection and effective regulation of designated agricultural zones by the Sleman Regency Government are imperative to ensure sustainable cultivation of essential food crops within the region and maintain the overall well-being of the agricultural landscape. The study contributes to advancing GIS-based land monitoring approaches and offers actionable insights for sustainable land use policy formulation in rapidly urbanizing regions. Strengthening policies for sustainable urban development in harmony with agricultural interests is pivotal to securing prosperous and balanced socio-economic growth.